Critique of Legislation in the Health Sector: A Review of Medical Waste Regulation in Indonesia - Yanuar Nur Rahmawanto (IBLAM Law Review)
Medical waste management in Indonesia has been a major concern in the healthcare sector, especially during the COVID-19 pandemic which increased the volume of medical waste. Although regulations such as Law No. 32 Year 2009 and Minister of Health Regulation No. 18 Year 2020 have been implemented, implementation faces challenges in the form of limited infrastructure, weak supervision, and high operational costs. This research uses normative juridical methods and case studies to examine the weaknesses of the regulations, implementation challenges, and impacts on public health and the environment. The results show a gap between regulations and field practices. The study recommends improved supervision, incentivisation, as well as the development of more detailed technical guidelines for medical waste management.